(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Pesticide residues in different crops, including food grains and vegetables are burning issues in Bangladesh. Therefore, the present study was conducted to analyze organophosphorus pesticide residues in three popular vegetables (cauliflower, hyacinth bean and yard long bean) collected from five local markets of Narsingdi district of Bangladesh. The collected vegetable samples were extracted and cleaned up using Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction technique and analyzed by Gas Chromatography (GC) equipped with Flame Thermionic Detector (FTD). A total of 45 vegetable samples were analyzed. Among the 15 analyzed samples of hyacinth bean, three samples (20 % of the total samples) contained pesticide residues above the EU-MRL and the remaining samples did not contain any detectable residues of the selected organophosphorus pesticides. In case of cauliflower, out of 15 analyzed samples, two samples (13% of the total number of samples) contained pesticide residues above the EU-MRL. In case of yard long bean, of the 15 analyzed samples, four samples (27% of the total number of samples) contained pesticide residues above the EU-MRLs. This study reveals the present status of pesticide residue contamination in the selected vegetables. Asian Australas. J. Biosci. Biotechnol. 2022, 7 (3), 114-121